RISK LIST IDENTIFICATION ENCOMPASSING TACIT KNOWLEDGE FOR VIRTUAL REALITY IN BUILDING PROJECTS IN JAKARTA - Aditya Pratama; Ryan Faza Prasetyo (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2023)
A high-rise building project can be considered as a high-risk project because the work items are quite a lot and high in the structure being built, the occupational health and safety (OHS) of construction plays an important role in the smooth implementation of a construction project. Construction OHS conducts safety briefing to all construction workers when they enter the construction project environment and every morning before the construction begins. Two information systems are used to inform the workers about the conditions and hazards in the construction projects, namely tacit knowledge and explicit knowledge. Therefore, safety induction is less effective and hinders the implementation of construction project work, where construction workers do not know situations that occur when carrying out a job socialized by OHS officers. In this problem, a simulation must be carried out before workers do their work, to carry out this simulation can be done with virtual reality technology. The research was conducted by distributing questionnaires to the OHS staff of construction projects in Jakarta while the data from the questionnaires were calculated. This study aims to find out a list of risks that are still relevant including tacit knowledge and obtained 11 work risks including tacit knowledge from 38 work risks for building construction projects in Jakarta. Keywords: Construction, OHS, Risk, Knowledge management, Virtual reality.